Role of glucometry in outpatient care, and managing patients with impaired carbohydrate metabolism - Tatiana Yu. Demidova; Vera N. Larina (LLC "MEDIAFORMAT", 2021)
The patient should become a full-fledged partner of the physician in the question of diabetes mellitus treatment. Patient's compliance and ability to perform structured self-monitoring have a direct impact on the treatment outcome. Patient education is a potential resource of treatment compliance. According to modern algorithms of care for patients with DM, patient training on blood glucose and blood pressure self-monitoring is a prerequisite for prevention and successful treatment of DM complications. Modern glucose meters, simple to use and comfortable, help to monitor blood glucose levels.